Fiscal Transparency, Gubernatorial Popularity, and the Scale of Government: Evidence from the States - James E. Alt; David Dreyer Lassen; David Skilling (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
We explore the effect of transparency of fiscal institutions on the scale of government and gubernatorial popularity using a formal model of accountability. We construct an index of fiscal transparency for the American states from detailed budgetary information. With cross-section data for 1986-1995, we find that - on average and controlling for other influential factors - fiscal transparency increases both the scale of government and gubernatorial popularity. The results, subjected to extensive robustness checks, imply that more transparent budget institutions induce greater effort by politicians, to which voters give higher job approval, on average. Voters also respond by entrusting greater resources to politicians where insittutions are more transparent, leading to larger size of government.
Keywords: 330; Öffentliche Finanzen; Finanzkontrolle; Föderalismus; USA